A history of Blacks in Kentucky : from slavery to segregation, 1760-1891 - Lucas, Marion Brunson, 1935- (Kentucky Historical Society, 2003)
A History of Blacks in Kentucky traces the role of blacks from the early exploration and settlement of Kentucky to 1891, when African Americans gained freedom only to be faced with a segregated society. Making extensive use of numerous primary sources such as slave diaries, Freedmen's Bureau records, church minutes, and collections of personalpapers, the book tells the stories of individuals, their triumphs and tragedies, and their accomplishments in the face of adversity. --